CHALLENGES IN THE PROFESSIONAL DEVELOPMENT OF PUBLIC SERVANTS AMID NEW REALITIES IN ADULT EDUCATION: CONCEPTUALIZATION OF COMPETENCE AND SYSTEM APPROACHES - Kalashnyk, Nadiia; Plakhotnyk, Olha; Khudoba, Oleksandra; Zayats, Diana; Mo, Guanxian (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article examines the multifaceted problems faced by public servants in their professional development within the dynamic conditions of adult education's new challenges within the conceptualisation of competence and the need for system approaches. The challenges in the professional development of public servants in the context of adult education necessitate a reimagining of competence and the adoption of system approaches. Conceptualising competence in a multidimensional way, including digital and interdisciplinary dimensions, is essential. System approaches that integrate training programs, promote continuous learning, coordinate government-wide efforts, and include diverse stakeholders offer a comprehensive solution to address the complex challenges faced by public servants in the contemporary landscape of adult education. By embracing these approaches, public sector organisations can ensure that their workforce is well-equipped to navigate the evolving demands of governance effectively. As practical material for the study, the authors of the article used theoretical and practical experience in training civil servants in Ukraine and the PR China (in particular, the experience of training management personnel in these countries both in the field of formal and non-formal education, as well as the very concept of “managing personnel”).